Factorisation de $a^n – b^n$ par $(a-b)$

Factorisation de $a^n-b^n$ par $(a-b)$

Factorisation de $a^n-b^n$ par $(a-b)$

 

Propriété

 

Soit $(a,b)inmathbb{C^2}$ et $ninmathbb{N^*}$,

$a^n-b^n=(a-b)displaystylesum_{k=1}^{n} a^{n-k};b^{k-1}$

pour $n=2$ :

$(a-b)displaystylesum_{k=1}^{2} a^{2-k};b^{k-1}=(a-b)(a+b)=a^2-b^2$

pour $n=3$ :

$(a-b)displaystylesum_{k=1}^{3} a^{3-k};b^{k-1}=(a-b)(a^2+ab+b^2)=a^3-b^3$

pour $n=4$ :

$(a-b)displaystylesum_{k=1}^{4} a^{4-k};b^{k-1}=(a-b)(a^3+a^2b+ab^2+b^3)=a^4-b^4$

 

Démonstration 

 

$(a-b)displaystylesum_{k=1}^{n} a^{n-k};b^{k-1} = displaystylesum_{k=1}^{n} a^{n-k+1};b^{k-1} – displaystylesum_{k=1}^{n} a^{n-k};b^{k}$

$(a-b)displaystylesum_{k=1}^{n} a^{n-k};b^{k-1}= displaystylesum_{j=0}^{n} a^{n-j};b^{j} – displaystylesum_{k=1}^{n} a^{n-k};b^{k-1}; textrm{(on a réindexé la première somme, avec j=k-1)}$

$(a-b)displaystylesum_{k=1}^{n} a^{n-k};b^{k-1}=a^{n-0};b^0 + displaystylesum_{j=1}^{n-1} a^{n-j};b^{j} – displaystylesum_{k=1}^{n-1} a^{n-k};b^{k} – a^{n-n};b^n$

$(a-b)displaystylesum_{k=1}^{n} a^{n-k};b^{k-1}=a^n-b^n$ QED